2007
DOI: 10.1055/s-2007-982562
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Cyclization of N-Alkynyl Carbamates

Abstract: Six different N-alkynyl carbamates containing Boc groups were prepared. Their gold(I)-catalyzed cyclization to oxazolinones proceeded radily at room temperature or even lower temperatures.Among gold-catalyzed reactions 2 the intramolecular oxyauration of C-C multiple bonds is an excellent tool for the formation of oxygen-containing heterocycles. The first example was the cycloisomerization of allenyl ketones or propargyl ketones, 3 similar results were obtained with 2-alkynyl-2-alken-1-ones. 4 Subsequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 6 publications
1
54
1
4
Order By: Relevance
“…[2] In 2004, we reported the use of N-propargyl carboxamides 1, having terminal alkynyl groups (Scheme 1, R 2 = H), for 5-exo-dig cyclizations, [3] and in 2007 we reported the 5-endo-dig cyclization of N-alkynyl carbamates. [4] These first two papers have initiated the development of an entire family of gold-catalyzed cyclizations involving carbonyl groups as nucleophiles to deliver different types of heterocycles. [5][6][7] Herein we report new findings on the cyclization of N-propargyl carboxamides having internal alkynyl groups.…”
mentioning
confidence: 99%
“…[2] In 2004, we reported the use of N-propargyl carboxamides 1, having terminal alkynyl groups (Scheme 1, R 2 = H), for 5-exo-dig cyclizations, [3] and in 2007 we reported the 5-endo-dig cyclization of N-alkynyl carbamates. [4] These first two papers have initiated the development of an entire family of gold-catalyzed cyclizations involving carbonyl groups as nucleophiles to deliver different types of heterocycles. [5][6][7] Herein we report new findings on the cyclization of N-propargyl carboxamides having internal alkynyl groups.…”
mentioning
confidence: 99%
“…[2] 2004 berichteten wir über die Verwendung von N-Propargylcarboxamiden 1 mit endständigen C-C-Dreifachbindungen (Schema 1; R 2 = H) für 5-exo-dig-Cyclisierungen [3] und 2007 über die 5-endo-dig-Cyclisierung von N-Alkinylcarbamaten. [4] Besonders diese ersten beiden Publikationen haben die Entwicklung einer ganzen Reihe von Gold-katalysierten Cyclisierungen ausgelöst, die auf Carbonylgruppen als Nucleophilen beruhen und verschiedenste Typen von Heterocyclen liefern. [5][6][7] Hier berichten wir über neue Beobachtungen zur Cyclisierung von N-Propargylcarboxamiden mit inneren C-C-Dreifachbindungen.…”
unclassified
“…It is also noteworthy that the previously reported 5-endo cyclization of the tert-butyloxycarbamate on the alkyne (Scheme 1) [7,8] did not significantly compete with this new transformation. The nucleophilic addition of the alkene moiety on the activated gold-alkyne complex seems to be a more favored process and only traces of oxazolones 14 could be observed when a gold complex was used as the catalyst.…”
Section: Resultsmentioning
confidence: 62%
“…The first study in this domain was made by Cossy and coworkers who described the gold(I)-catalyzed cycloisomerization of ene-ynamides into 2-azabicylco[3.1.0]hexanes [6]. Later on, the group of Hashmi [7] and our group [8] independently reported that N-alkynyl tert-butyloxycarbamates 1 could be converted in the presence of a gold(I) complex into a range of functionalized oxazolones 2 (Scheme 1). More recently, Hashmi and coworkers reported the elegant synthesis of dihydroindole and tetrahydroquinoline derivatives using electron-deficient ynamides as the substrates [9].…”
Section: Introductionmentioning
confidence: 99%